ANALISIS PROMOSI JABATAN STRUKTURAL ESSELON III DAN IV DI KANTOR BAPPEDA KABUPATEN PARIGI MOUTONG - Toana, Mustika Sari (Katalogis, 2017)
This study aimed to describe and analyze the structural position promotion of third and fourth echelon at Parigi Moutong Local Development Planning Agency. The method used in this study was descriptive qualitative method. The social situation in this study was the work environment of Parigi Moutong Local Development Planning Agency as well as the interactions occured in it. The informants in this research were the head of the Advisory Board for Position and Rank’s team and from the Organizing Committee’s secretariat, amounting to 3 (three) persons. The informants were determined using purposive method or selected purposively, for they were the subjects who mastered the problems relating to the purposes of this research. The results showed that in the structural position promotion at Parigi Moutong Local Development Planning Agency, based on the theory of SP. Hasibuan, the experience or seniority aspect had been noticed but still needed to be enhanced, meanwhile the work skill aspect, could be said, had not been running well because the indicator components had not been used entirely as considerations in the promotion process. Also, the combined aspects of experience and skill had not been noticed in the promotion process so that it had not been implemented well. The promotion process was still affected by Spoil and Nepotism System. Meanwhile, in the implementation of competency test based on the Law Number 5 Year 2014 on State Civil Apparatus, the local Organizing Committee had not been carrying out its tasks properly due to its inconsistencies to the administrative conditions issued for the participants of the test. The structural position promotion of third echelon had not been fully in accordance with the procedures, for the requirements for participating the competency test of administrator position, like having ranked Class IIId and having participated in Fourth Leader Training or having educated in the second stratum, were not applied in the reality because there were still some participants, who ranked Class IIIb and IIIc as well as having never participated in Fourth Leader Training, participated in the test. While, the competency test for superintendet position (fourth ecelon) was not carried out by the Committee for various reasons, the main reason was ‘no budget’ so it was not implemented. The implementation of this competency test was eventually just a mere trial where the local Committee was not transparent to the results of the competency test by not announcing it publicly so it was never known who was eligible and who was not eligible for being inaugurated as the position promoted. It raised questions and disappointments from the majority of participants, for not knowing the test results, whether meeting the standards prescribed for occupying the third echelon position or not.